Interactions of Colorectal Cancer, Dietary Fats, and Polymorphisms of Arachidonate Lipoxygenase and Cyclooxygenase Genes: A Literature Review - Gholamalizadeh, Maryam; Majidi, Nazanin; Tajaddod, Shirin; Abdollahi, Sepideh; Poorhosseini, Seyed Mohammad; Ahmadzadeh, Mina; Naimi Joubani, Mohammad; Mirzaei Dahka, Samaneh; Shafaei, Hanieh; Hajiesmaeil, Mogge; Alizadeh, Atiyeh; Doaei, Saeid; et al. (Frontiers in Oncology, 2022)
Objective: Genetic and dietary factors play important roles in the development of colorectal cancer (CRC). However, the underlying mechanisms of the interactions between CRC, gene polymorphisms, and dietary fat are not clear. This review study aimed to investigate the effects of polymorphisms of arachidonate lipoxygenase (ALOX) and cyclooxygenase (COX) genes on the association between CRC and dietary fat. Methods: All the related papers published from 2000 to 2021 were collected from different databases such as PubMed, Science Direct, Scopus, and Cochran using related keywords such as colorectal cancer, ALOX, COX, polymorphism, and dietary fat. Non-English and unrelated documents were excluded. Results: Some single-nucleotide polymorphisms (SNPs) in the ALOX and COX genes, such as rs2228065, rs6413416, and rs4986832 in the ALOX gene and rs689465 in the COX gene may play significant roles in the association between the risk of CRC and dietary fats. The effects of dietary fatty acids on the risk of CRC may be influenced by SNPs of ALOX and COX genes. Conclusion: Some polymorphisms of the ALOX and COX genes may have important roles in the effects of dietary fat on the risk of CRC. If future studies confirm these results, dietary recommendations for the prevention of colorectal cancer should be personalized based on the genotype of ALOX and COX genes.